Cells on Ice. - Dumiak, M.
Researchers at the Fraunhofer Institute for Biomedical Engineering in St. Ingbert, Germany, are developing an automated industrial scale cell archive, in which millions of cell specimens can be frozen for decades, waiting to be reanimated when needed. Despite the current controversy surrounding stem cell research, these researchers aim to design a compact storage area for the cell samples and to develop a system for securely and precisely automating specimen handling. A key component of the system is the flash memory chip which has been modified to work in extreme cold. Locating all relevant information directly with the specimens obviates central storage of vast amounts of highly personal information, eliminates the possibility of mismatches between central databases and samples, and facilitates automated handling and manipulation of samples
Keywords: Automated industrial scale cell; Automated specimen handling; Automating specimen handling; Central databases; Central storage; Compact storage area; Flash memory chip; Personal information